HOW CAN THE PUBLIC BE BETTER PROTECTED AGAINST COVID-19? - Gan, Connie CR; Dwirahmadi, Febi (Jurnal Berkala Epidemiologi, 2020)
INTRODUCTION The response to the COVID-19 pandemic is a tragic aberration gripping the world. As the disease evolves, uncertainty and fear of harm rise, which can significantly diminish community health and wellbeing. This article stresses the importance of public health preparedness in overcoming social and health risks associated with public panic. Since the COVID-19 outbreak began in late 2019, the numbers of people affected and fatalities continue to mount, causing panic and crippling vital economic and social activities. Authorities have failed to prevent inaccurate and misleading headlines that agitate the public and impinge on public communication. Fake news and rumors about magical products claiming to cure the virus abound. Additionally, people assumed emergency preparation meant stockpiling resources. Amid growing fears, consumers raided supermarkets and pharmacies for supplies, from masks to hygiene products, and people have fought over protective gear as tensions flared among anxious customers. When general panic starts driving political decision-making, public health professionals may be unable to implement strategies based on informed decisions. Researchers argue that government secrecy and non-transparency diminish people’s confidence and trust, creating panic (Wilson et al., 2007). Even naming the disease possibly triggered epidemic-related trauma and the ensuing public mistrust and disbelief of authorities; the panic has also sparked a wave of racial prejudice (Titanji, 2020). Although a series of emerging and re-emerging infectious diseases, from Avian flu to Zika virus, may have created more public awareness, whether leaders can translate this newfound awareness into meaningful policies and action is debatable. Globally, attention is growing on responses from state leaders, as some try to downplay the epidemic’s severity to maintain "business as usual”. In early March 2020, the Indonesian government was still in a state of denial and was attempting to convince the general public that the country was free from COVID-19 (Lindsey & Mann, 2020) Instead, currently confirmed cases are growing rapidly, suspected cases are far above the testing capacity, and case fatality is at an alarming rate. In contrast, several countries took drastic action by declaring travel restrictions and locking down cities. As an example, New Zealand decided to implement level-4 measures, with strict movement restrictions, not long after they confirmed their first case on 28 February 2020; they have recently begun a gradual exit from coronavirus lockdown (Knight, 2020). The public expects leaders to curb the spread of COVID-19 responsibly, appropriately, effectively, and proactively. Meanwhile, leaders are urging the public to stay calm and adopt new norms during this rapidly evolving situation. This crisis is not limited to any individual and requires cooperation rather than a unilateral response. DISCUSSION How to do this? A critical approach to pandemics is to ensure the preparedness of both healthcare capacity and public health systems (Jain, Duse, & Bausch, 2018). To respond to emergency needs”to have the capacity to treat rapidly increasing numbers of COVID-19 patients”it is important for each country to have existing policies and action plans for healthcare facilities to temporarily expand service capacity, cancel or postpone elective procedures, and engage in rapid intervention to conserve medical supplies, including personal protective equipment (Gan, Tseng, & Lee, 2020). Measures including recalling recently retired healthcare workers and providing drive-through services for chronic disease medications have been implemented to lessen pressures on hospitals (Wang, Ng, & Brook, 2020). While healthcare capacity is the ability to care for patients with COVID-19, the public health system aims to prevent people from being infected and mitigating the health risks associated with COVID-19. The public health system is important for strengthening community vigilance by promoting effective sanitation, a healthy lifestyle, and food safety, and preventing injuries, inequality, and violence. This involves not only healthcare professionals, but also well-planned strategies that consider various stakeholders’ perspectives and concerns (Glik, 2007). Despite the lockdown, we have seen healthcare workers and people in the community providing the basic essentials for those in need”from food, Personal Protective Equipment (PPE), mental health support, and evidence-based research communication, to virtual musical performances and concerts. Organizations in the virtual sphere, including WhatsApp (WhatsApp Inc, 2020) and TikTok, are partnering with health agencies to increase accessibility to health information. The best outbreak response is a collective response (Gille & Brall, 2020), which could effectively contain the disease and the panic caused by the disease. People naturally experience fear when dealing with a catastrophic event. This unprecedented threat triggered panic purchasing or falling for viral hoaxes, which reflects misconceptions about the problem, most likely because people lack trust in the measures taken (Heide, 2004), When designing and implementing public health measures, we must ensure we do not just acknowledge that, but actively engage relevant stakeholders. In an age of uncertainty, community solidarity and collective action are key to maintaining community vigilance against the crisis (Aldrich et al., 2015).